Development of Biodegradable Packaging Materials from Bio-Based Raw Materials - Maraz, Kazi M.; Karmaker, Nanda; Meem, Romana Afrose; Khan, Ruhul A. (Journal of Research Updates in Polymer Science, 2019)
Seaweed, creatures and cellulose based packaging materials are biodegradable and promising natural polymer and their films can be prepared from bio-based raw materials. This article reviews the basic information and recent developments of both seaweed, creatures, cellulose and plant based biopolymer materials as well as analyses the feasible formation of seaweed/creatures/cellulose/plant based biodegradable packaging films which possesses excellent mechanical strength and water resistance properties. Moreover, bio-based packaging films can prolong a product’s shelf life while maintaining its biodegradability. Additionally, the films show potential in contributing to the bio-economy. These type of bio-based materials exhibit interesting film-forming properties that can be used in biomedical application and for making composites for packaging. Bio-based films can be used for the large-scale applications in food packaging in place of synthetic petroleum based non-degradable packaging. Bio-based films have the potential to be used in textile and decoration paper industries also. Currently, bio packaging gains huge attention to the scientist and general people because this type packaging materials are environmental friendly products. Some of the viewpoints are highlighted for future developments and applications.